Data protection for virtual data centers - Buffington, Jason (Wiley India, 2010)
"Essential information on how to protect data in virtual environments! Virtualization is changing the data center architecture and as a result, data protection is is quickly evolving as well. This unique book, written by an industry expert with over eighteen years of data storage/backup experience, shows you how to approach, protect, and manage data in a virtualized environment. You'll get up to speed on data protection problems, explore the data protection technologies available today, see how to adapt to virtualization, and more. The book uses a "good, better, best" approach, exploring best practices for backup, high availability, disaster recovery, business continuity, and more. Covers best practices and essential information on protecting data in virtualized enterprise environmentsShows you how to approach, protect, and manage data while also meeting such challenges as return on investment, existing service level agreements (SLAs), and more Helps system and design architects understand data protection issues and technologies in advance, so they can design systems to meet the challengesExplains how to make absolutely critical services such as file services and e-mail more available without sacrificing protectionOffers best practices and solutions for backup, availability, disaster recovery, and othersThis is a must-have guide for any Windows server and application administrator who is charged with data recovery and maintaining higher uptimes"--